The Influence of Social Media on Consumer Purchase Intentions: Like Behavior as a Moderator - Mercyano Christi; Shellyana Junaedi (Syntax Corporation Indonesia, 2021)
his study aims to analyze the effect of e-WOM, brand image, brand awareness on perceived value and purchase intention with liking behavior as moderation. The object of this research is the Lactona brand on social media. Valid respondents in this study amounted to 145 respondents. Data were collected through an online questionnaire. Consumers often use social networking sites that are studied through electronic word of mouth references, consumers can easily obtain various types of brand information that drive purchase intention. Based on the perspective of consumer behavior, a research model was developed to determine what factors influence consumer value perceptions and purchase intentions on social media. Of all the variables, only liking behavior is insignificant. The results of this study can be used as a reference for further research on research development.